2016
DOI: 10.4103/0300-1652.182082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome among HIV-infected patients in Ghana: A cross-sectional study

Abstract: Background:Prevalence of metabolic syndrome (MetS) in HIV-infected patients is very limited in the Ghanaian setting and may vary across the globe by the different study populations and criteria used.Aim:We investigated the prevalence of MetS among HIV-infected patients receiving highly active antiretroviral therapy (HAART) at the St. Dominic Hospital, Akwatia, Ghana.Patients and Methods:This cross-sectional study recruited 433 HIV-infected patients (294 on HAART and 139 HAART-naïve) from the period of February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
8
25
0
9
Order By: Relevance
“…The prevalence rate of dyslipidemia among HIV patients on ART in this current study was 31.1% with low HDL-C and high TC levels being the commonest lipid abnormalities. The observed prevalence of dyslipidemia is comparable to the range of reports from previous studies by Obirikorang et al [9] and Ngala et al [10] in Ghana and Kodogo et al [10] in Zimbabwe. However, it is lower compared to 78.9% prevalence rate reported by Limas et al [39] in a cross-sectional study among Brazilian HIV individuals on ART.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence rate of dyslipidemia among HIV patients on ART in this current study was 31.1% with low HDL-C and high TC levels being the commonest lipid abnormalities. The observed prevalence of dyslipidemia is comparable to the range of reports from previous studies by Obirikorang et al [9] and Ngala et al [10] in Ghana and Kodogo et al [10] in Zimbabwe. However, it is lower compared to 78.9% prevalence rate reported by Limas et al [39] in a cross-sectional study among Brazilian HIV individuals on ART.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of dyslipidemia is reportedly higher in people living with HIV due to the effect of ART in Ghana [9][10][11]. The severity of dyslipidemia and the typical pattern of the lipid profile differ between and within the classes of antiretroviral (ARV) agents [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found a higher prevalence of MS in HAART-exposed patients compared to naive patients (29.5% vs 23.8%) with no significant statistical difference. If numerous studies have objectified a significant predominance of MS in exposed subjects [18] [22] [23] [27], our result could be linked to the small proportion of naive patients in our sample (15.1%). Our study, for example, did not show any association between duration on HAART and MS confirming the conclusions of some authors [26] [28] [29].…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it was essential that at least one site showed lipoatrophy, i.e., visible loss of fat in peripheral regions (arms or legs) or face accompanied or not by lipohypertrophy, i.e., accumulation of fat in the abdominal region, dorsal gibbosity, or gynecomastia 12 .…”
Section: Study Groupmentioning
confidence: 99%